Therapeutic Approach and Prevention in Recurrent Acute Biliary Pancreatitis - Forlano, Immacolata; Lapolla, Francesco; Fersini, Alberto; Tartaglia, Nicola; Ambrosi, Antonio; Neri, Vincenzo (JOP. Journal of the Pancreas, 2012)
Context Acute biliary pancreatitis (ABP) is caused by alteration of the papillary patency. Objective Normal transpapillar flux and cleaning of the common biliary duct (CBD) may prevent potentially avoidable recurrent pancreatitis. Methods In the period from September 1999 to December 2011 we treated 276 ABP (60 severe, 216 mild/moderate): 188 (72%) with first attack and 73 (28%) with recurrent ABP (second or further attack). Patients with recurrent pancreatitis had not undergone, in previous hospital stay elsewhere, the evaluation and, if necessary, treatment of papillary obstacle and/or CBD stones or sludge. In our hospital all patients underwent the treatment of ABP completed with cholecystectomy. All patients, after discharge, were introduced in a follow-up program (clinical and US control) after 180 days and 1 year. Results In the follow-up of recurrent pancreatitis we controlled 42 patients (57%; 31 lost). Follow-up results showed, beside the absence of recurrent acute episodes, stable normalization of laboratory cholestasis tests and US control. The same controls in 90 patients (48%) with a first attack of acute pancreatitis resulted normal in absence of a new acute episode. Conclusions Recurrent ABP is caused by persistent papillary obstacle. Therefore, we confirm therapeutic validity of instrumental control (US/MRCP) and possible treatment of papillary or biliary lithiasis obstacle for prevention of recurrent ABP.